Equals [compact disc] - Sheeran, Ed, 1991- (Asylum Records UK, a division of Atlantic Records, 2021)
The fourth installment in Ed Sheeran's symbol album series finds him taking stock of his life and the people in it, as he explores the varying degrees of love, loss, resilience, and fatherhood, while also processing his reality and career.